Additions to Crassiparies and Neobrevicollum (Neohendersoniaceae, Pleosporales) associated with woody hosts in Southwest China - Lu, Yu-Hang; Zhang, Sheng-Nan; Du, Hong-Zhi; Cheewangkoon, Ratchadawan; Liu, Jian-Kui (Phytotaxa, 2024)
During an investigation of ascomycetous fungi from decaying wood in southwest China, seven taxa with sexual morphs were found to be saprobic from terrestrial habitats. These taxa were identified based on morphology, phylogeny, and cultural characteristics. The morphology and phylogenetic evidence placed these new fungal collections in Neohendersoniaceae, distributing in the genera Crassiparies and Neobrevicollum. The phylogenetic analyses of a combined ITS, LSU, SSU, RPB2, and TEF1-α sequence dataset also confirmed their taxonomic placement. A new species, Neobrevicollum biancaeae is introduced to accommodate the two taxa, which have thin-walled ascomata without ostiole, and smaller asci and ascospores compared to the type species, N. oleae. The other five samples were identified as Crassiparies quadrisporus and N. oleae representing three and two taxa, respectively. The identification and establishment of these species are justified based on morpho-molecular analyses. In addition, the new host records of C. quadrisporus and N. oleae were reported. Detailed descriptions and illustrations are provided for collected taxa. This study contributed to the microfungal diversity in Southwest China.